Examined lymph node counts affected the staging and survival in cervical cancer: a retrospective study using the SEER and Chinese cohort - Tao Guo; Yuxi Zhao; Jia Zeng; Jian Li; Enyu Tang; Lingying Wu (Annals of Medicine)
Background The impact of examined lymph node (LN) count on survival in cervical cancer remains understudied, with no consensus on the optimal number required.Objectives We aimed to investigate the role of LN count in postoperative pathological evaluation for cervical cancer patients undergoing surgery.Methods Data from the US SEER database and a retrospective Chinese cohort were analyzed. Multivariable logistic and Cox regression models assessed LN positivity detection and overall survival (OS), respectively. Smoothing spline curves and Chow tests identified structural change points in hazard ratios and LN-positive ratios.Results Among 14,133 SEER and 2,811 Chinese cases, higher LN counts correlated with increased detection of positive LNs (OR: 1.040, 95% CI: 1.019–1.062) and improved OS (HR: 0.990, 95% CI: 0.984–0.996). Structural change points occurred at 20 LNs for LN-negative patients and 13 LNs for LN-positive patients (both P < 0.001). An elevated LN-positive ratio (positive/examined LNs) strongly predicted worse OS (HR: 4.208; 95% CI: 1.454–12.181).Conclusions An increased number of examined LNs significantly contributes to the detection of positive LNs and improved patient survival. For patients with claimed LN-negative and LN-positive disease, a minimum examination of 20 and 13 LNs, respectively, is recommended to ensure adequate LN evaluation. The LN positive ratio is a strong prognostic indicator in patients with LN-positive disease.